Cultural Agency in Postcolonial Interfaith Dynamics: The Transition from Co-Existence to Pro-Existence in Islam–Hindu Relations in Kediri - Huda, M Thoriqul; Rosyid, Asyhad Abdillah; Waeno, Mahamadaree (Tribakti: Jurnal Pemikiran Keislaman, 2026)
Islam–Hindu relations in Kediri are often portrayed as a form of harmonious coexistence, yet such a view risks overlooking the social mechanisms that actively produce and sustain interfaith stability. This study examines how local cultural practices, particularly the Ogoh-ogoh tradition, function as a form of cultural agency that shapes interreligious dynamics in a postcolonial setting. Employing a qualitative approach with an ethnographic orientation, data were collected through in-depth interviews, participant observation, and fieldnotes in Sekaran and Bedali villages, Kediri Regency. The findings reveal that Ogoh-ogoh operates not only as a Hindu religious celebration but also as a shared public arena that enables interfaith encounters and repeated cooperative practices involving Muslim residents. This participation goes beyond passive tolerance, demonstrating a shift from co-existence toward pro-existence, where the majority community actively supports the minority’s religious expression and public visibility. The study further shows that tradition serves as a mechanism of vernacular governance by strengthening social integration, reproducing inclusive values across generations, and mitigating potential tensions through locally embedded social capital. The article contributes a cultural agency–based transition model that explains how interfaith relations can move from recognition and non-interference to active solidarity and collaborative engagement. This model offers a grounded theoretical contribution to postcolonial interfaith studies and provides empirical insight into how local communities in Indonesia maintain inclusive public spheres through lived cultural practices.